THE PROBLEMS OF STATE REGULATION OF SMALL BUSINESS IN GEORGIA - ABESADZE, Ramaz; KAKULIA, Eteri (CENTRAL ASIA AND THE CAUCASUS, 2009)
The former Soviet republics, including Georgia, achieved their state independence, which brought with it a multitude of problems. The former economic ties broke down and there was not enough qualified personnel to promote the development of a market economy, so many enterprises ceased to exist, and the country’s economy collapsed. The main task was to restructure the national economy. The republic’s government did all it could to form a market economy in the country, but these attempts were not crowned by success. The population spontaneously launched into small business, but nor did this do anything to improve the economy. World experience shows that small business can play a significant role in resolving many problems; it plays a vital part in reducing unemployment and strengthening economic stability as a whole. At the stage of the post-communist transformation the advantages of small business are most important and can be enhanced with the help of a streamlined mechanism of state support. Small business is important due to the influence it has on macroeconomic indices (GDP, employment, budget revenues and expenditures, import, export, inflation, and so on). Small business is one of the main sources for developing and stabilizing the economic system as a whole. It also provides a quick return on money invested. In developed countries, almost half of the able-bodied population is employed in small business; it accounts for approximately 50% of all the products manufactured in the country.